2002
DOI: 10.1016/s0886-3350(01)01094-x
|View full text |Cite
|
Sign up to set email alerts
|

Speed of capsular bend formation at the optic edge of acrylic, silicone, and poly(methyl methacrylate) lenses

Abstract: Capsular bend formation progressed in the same fashion but at significantly different speeds among the IOLs, suggesting that the process depends on IOL material and design. Fast, early capsular bend formation may be 1 reason AcrySof and PhacoFlex II IOLs prevent PCO statistically better than PMMA IOLs. The results indicate that PCO is prevented by the sharp capsular bend created by sharp optic edges and by quick bend formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
81
1
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 13 publications
3
81
1
9
Order By: Relevance
“…Also, in a study by Nagata et al [16] , and another by Oshika et al [17] , the adherence force between the IOL and the capsule, attributable to integrins and cadherin adhesion molecules expressed by the LECs [18] , was found to be greater with acrylic than with silicone IOLs. This adherence was found to occur even faster with the hydrophobic acrylic than with silicone and PMMA IOLs [14] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, in a study by Nagata et al [16] , and another by Oshika et al [17] , the adherence force between the IOL and the capsule, attributable to integrins and cadherin adhesion molecules expressed by the LECs [18] , was found to be greater with acrylic than with silicone IOLs. This adherence was found to occur even faster with the hydrophobic acrylic than with silicone and PMMA IOLs [14] .…”
Section: Discussionmentioning
confidence: 91%
“…The sharp square edge of the lens optic is another attribute of the acrylic lens and perhaps the most important in producing this characteristic appositional relationship. Nishi et al [14] showed that capsular bend formation around the IOL implant occurs earlier with hydrophobic acrylic IOLs (Acrysof) than with silicone and PMMA IOLs. Boyce et al [15] , using a mathematical model, found that squareedged optic profi les exert a higher pressure on the posterior capsule than IOLs with round-edged optic profi les.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of PCO varies depending on the age at surgery, surgical technique retained soft lens matter, post-operative uveitis, IOL optic material, and IOL design. 7,8,[11][12][13][14] The inclusion of only normal eyes apart from senile cataract, the nature of the prospective randomized single surgeon design of this trial, and the use of standardized surgical procedure, and medication eliminate other explanations for our results. Therefore, the differences in PCO among the study groups can probably be ascribed to IOL material and design.…”
Section: Discussionmentioning
confidence: 99%
“…Strong adhesion of IOLs to the lens capsule, as is described for hydrophobic acrylic IOLs, is one of the factors that is supposed to reduce PCO [17]. But this IOL feature seems to have the disadvantage of increased LEC adhesion to the anterior surface and ACO development.…”
Section: Discussionmentioning
confidence: 99%